Bridging the gap between neuroimaging and neuronal physiology - Kim, Dae-Shik (Image analysis and stereology, 2002)
Despite the fact that blood oxygenation level dependent (BOLD) functional magnetic resonance imaging (fMRI) studies have become ubiquitous and are of ever increasing importance for clinical and basic neurosciences, the fundamental relationships between BOLD and the underlying neuronal physiology are not understood. 'This raises severe concerns about the validity of BOLD contrast per se, and the conceptual frameworks currently employed in interpreting cognitive neuroimaging data. In order to expand the explanatory power of functional MRI data, several crucial questions will have to be addressed. The two most important questions are: First, what is the ultimate spatial resolution of fMRI? And secondly, what is the "neural correlate" of functional MRI? This article attempts to compile a series of results from our and other laboratories, suggesting that both the questions of "spatial specificity" and "neural correlate" might be within the reach of a tentative solution, thus finally bridging the gap between functional neuroimaging and neuronal physiology.
Keywords: Magnetic resonance imaging; Magnetna resonanca; Nevroni; Visual cortex; Vidna skorja; Blood supply; Neurons; Mačke; nevrofiziologija; Cats; jedrska magnetna resonanca